Game Digital “Ramadan Adventure” - Muhammad Fajri; Dwi Mutia Sari (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This study aims to develop an Android-based educational game that focuses on learning about fasting. This game is designed to provide a fun, exciting and educational interactive experience for users, especially children aged 6-12 years who want to learn about fasting in the month of Ramadan. The method used in developing this game is the Design Thinking method, which involves five stages of the process, namely (emphasize) understanding, (define) definition, (ideate) idea, (prototype) prototype and, (test) testing. In research and data collection, the authors used questionnaires, and observations as primary data, and secondary data including literature and internet reviews. Making educational games is developed using the game engine Construct 2. The games developed are only limited to prototypes so that more implementation and application is needed, therefore further research is still needed to perfect this Ramadan Adventure game. The results of this study are expected to make a positive contribution in the development of educational games that are useful for learning about fasting. This game can be used as an interesting and interactive educational tool to help users better understand and practice fasting. In addition, this research also has the potential to become a foundation for the development of other Android-based educational games that focus on religious and cultural learning.